(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Social, political, economic and cultural changes taking place at the global level play an important role in leading to new trends and challenges in the field of management education. To make education more effective, digital media is moving very fast nowadays. Artificial intelligence (AI) and Information and Communication Technology (ICT) are digital techniques are very important in enhancing the quality of education. The use of AI and ICT in management education emphasizes more and more to promote student-centered education. The management education highlights the use of ICT and AI to make student outcomes efficient and effective. The world is moving very fast in the field of digital media and according to the way in which the role of AI and ICT is becoming increasingly important and will develop more new dimensions in the future. AI and ICT will revolutionize the field of education. There will be definitely be new uses in the technology sector in the coming future, there will be new tools and techniques in AI and ICT which will be more powerful and there will be more new things in education which is probably beyond our imagination. In this paper, we describe why we need AI and ICT in management education, types of AI and ICT applications, their impact on education system, uses of AI and ICT in recent management and also discuss about future of AI and ICT. Finally we described growth of AI and ICT knowledge and practice.